2015
DOI: 10.1051/0004-6361/201423584
|View full text |Cite
|
Sign up to set email alerts
|

Galactic planar tides on the comets of Oort Cloud and analogs in different reference systems. I.

Abstract: A comet cloud analog of Oort Cloud, is probably a common feature around extra solar planetary systems spread out across the Galaxy. Several external perturbations are able to change the comet orbits. The most important of them is the Galactic tide which may re-inject the comets towards the inner part of the planetary system, producing a cometary flux with possible impacts on it. To identify the major factors that influence the comet injection process we organized the work into three papers. Paper I is devoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…24 Distribution of comet orbits in an inertial frame on the Galactic plane with the same perihelion and increasing aphelions at different Galactic longitudes (see text) before switching on the Galactic tides (Masi et al, 2003;Masi et al, 2009). The initial not perturbed orbits here considered are similar to those taken into account by De Biasi et al (2015).…”
Section: The Contribution Of Dynamical Galaxy Components To the Tidal...mentioning
confidence: 96%
See 4 more Smart Citations
“…24 Distribution of comet orbits in an inertial frame on the Galactic plane with the same perihelion and increasing aphelions at different Galactic longitudes (see text) before switching on the Galactic tides (Masi et al, 2003;Masi et al, 2009). The initial not perturbed orbits here considered are similar to those taken into account by De Biasi et al (2015).…”
Section: The Contribution Of Dynamical Galaxy Components To the Tidal...mentioning
confidence: 96%
“…Moreover they will certainly be non negligible in presence of spiral arm perturbations, as also Kaib et al (2011) have already pointed out and it has been confirmed in the preliminary results of De Biasi ( 2014). An interesting contribution to this problem comes out by the work of De Biasi et al (2015). They consider only the effects of Galactic planar tides but at two different distances from the Galactic center: 4 kpc and 8 kpc, assuming the last one as the current solar position.…”
Section: Galactic Planar Tides On the Comets Of Oort Cloud And Analogsmentioning
confidence: 99%
See 3 more Smart Citations